Bi‐allelic mutation in SEC16B alters collagen trafficking and increases ER stress. Issue 4 (14th March 2023) - El‐Gazzar, Ahmed; Voraberger, Barbara; Rauch, Frank; Mairhofer, Mario; Schmidt, Katy; Guillemyn, Brecht; Mitulović, Goran; Reiterer, Veronika; Haun, Margot; Mayr, Michaela M; Mayr, Johannes A; Kimeswenger, Susanne; et al.
Abstract: Osteogenesis imperfecta (OI) is a genetically and clinically heterogeneous disorder characterized by bone fragility and reduced bone mass generally caused by defects in type I collagen structure or defects in proteins interacting with collagen processing. We identified a homozygous missense mutation in SEC16B in a child with vertebral fractures, leg bowing, short stature, muscular hypotonia, and bone densitometric and histomorphometric features in keeping with OI with distinct ultrastructural features. In line with the putative function of SEC16B as a regulator of trafficking between the ER and the Golgi complex, we showed that patient fibroblasts accumulated type I procollagen in the ER and exhibited a general trafficking defect at the level of the ER. Consequently, patient fibroblasts exhibited ER stress, enhanced autophagosome formation, and higher levels of apoptosis. Transfection of wild‐type SEC16B into patient cells rescued the collagen trafficking. Mechanistically, we show that the defect is a consequence of reduced SEC16B expression, rather than due to alterations in protein function. These data suggest SEC16B as a recessive candidate gene for OI. Synopsis: The newly found mutant SEC16B causes type I collagen accumulation in the ER. This in turn leads to increased ER stress, autophagosome numbers and enhanced apoptosis. In addition, there is alteration of secreted COL1A1 in the SEC16B mutated cells. SEC16B homozygous mutation was identified in a boy with moderate osteogenesis imperfecta. The mutation reduces the expression of SEC16B mRNA. SEC16B mutant cells accumulate type I procollagen in the ER due to a secretory trafficking defect. SEC16B is a candidate gene for osteogenesis imperfecta. This study uncovers a new role for the SEC16B protein in the ER to Golgi Apparatus trafficking. Abstract : The newly found mutant SEC16B causes type I collagen accumulation in the ER. This in turn leads to increased ER stress, autophagosome numbers and enhanced apoptosis. In addition, there is alteration of secreted COL1A1 in the SEC16B mutated cells.